Electrochemistry of N4 Macrocyclic Metal Complexes Volume 2: Biomimesis, Electroanalysis and Electrosynthesis of MN4 Metal Complexes - Zagal, Jose H.; Bedioui, Fethi; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This new edition describes the state of the art regarding metal complexes of N4-ligands, such as porphyrins and phthalocyanines. Volume 2 focuses on the electro assisted use of N4 complexes as biomimetic models for studying several biological redox processes. It focuses on molecular oxygen transport and catalytic activation to mimic monooxygenase enzymes of the cytochrome P450 in particular. It also examines N4 complexes' use as catalysts for the oxidative degradation of various types of pollutants (organo-halides, for example) and residual wastes. The remarkable activity of these complexes towards a large number of significantly relevant biological compounds makes them excellent candidates as electrode modifiers for electrochemical sensing. This volume also discusses applications of N4 Macrocyclic Metal Complexes to photoelectrochemistry and photocatalysis, and concludes with an exciting section on Electrosynthesis of N4.
Biomimesis -- Supramolecular models of metallo-enzyme active sites -- Supramolecular hybrid organic/inorganic nanomaterials using metalloporphyrins and analogous macrocycles -- Catalytic Pathway of Human Metabolic Cytochrome P450s -- Electroanalysis and electrochemical sensors -- Applications of MN4 macrocyclic metal complexes in electroanalysis -- Spectroelectrochemical Studies of Novel metallophthalocyanines -- The electroanalysis and catalysis of hydrazine oxidation promoted by MN4 macrocyclics -- Electroanalysis using MN4 complexes as electrode modifiers -- Tuning the redox activity of MN4 complexes to match the highest electrocatalytic activity toward the oxidation of thiols -- The electrochemical oxidation of organic pollutants on electrodes modified with metallophthalocyanines -- Organization and Photoelectrochemical Reactivity of Water-Soluble Metalloporphyrins at the Liquid/Liquid Interface -- Electrosynthesis of N4 -- Design and electropolymerization of spirobifloroenylporphyrins -- Electrochemical pathways for the synthesis of porphyrin oligomers -- Electrochemical synthesis of cyclo(n)pyrrole.
Keywords: Electrochemistry; Energy storage; Materials -- Analysis; Bioorganic chemistry; Electrochemistry; Mechanical and Thermal Energy Storage; Characterization and Analytical Technique; Bioorganic Chemistry